(untitled) (LEGAL DIALOGICA, 2025)
This study aims to determine and analyze the legal basis governing firearm ownership in Indonesia, especially with regard to the Emergency Law. As well as to determine and analyze the extent of public awareness regarding regulations governing firearms ownership and their impact on the level of illegal firearms ownership in Indonesia. This research uses normative legal research methods with statutory and conceptual approaches. The data sources in this study consist of primary legal materials such as laws relating to firearms ownership, as well as secondary legal materials such as books and scientific journals. The analysis is conducted with a qualitative approach to explore the applicable legal aspects and obstacles in the implementation of regulations regarding firearm ownership. The results of this study show that the legal basis governing firearm ownership in Indonesia, especially Emergency Law Number 12 of 1951, provides severe criminal sanctions for violations, including the death penalty and life imprisonment. Public awareness regarding firearm ownership regulations is still low, which contributes to the high rate of illegal firearm ownership. As well as law enforcement against illegal firearms possession at various obstacles, including surveillance permits from the police and minimal public compliance in surrendering illegal firearms. Abstrak: Penelitian ini bertujuan untuk mengetahui dan menganalisis dasar hukum yang mengatur kepemilikan senjata api di Indonesia, terutama yang berkaitan dengan Undang-Undang Darurat. Serta untuk mengetahui dan menganalisis sejauh mana kesadaran masyarakat mengenai peraturan yang mengatur kepemilikan senjata api serta dampaknya terhadap tingkat kepemilikan senjata api ilegal di Indonesia. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Sumber data dalam penelitian ini terdiri dari bahan hukum primer seperti undang-undang yang berkaitan dengan kepemilikan senjata api, serta bahan hukum sekunder seperti buku dan jurnal ilmiah. Analisis dilakukan dengan pendekatan kualitatif untuk menggali aspek hukum yang berlaku serta hambatan dalam implementasi peraturan mengenai kepemilikan senjata api. Hasil penelitian ini menunjukkan bahwa dasar hukum yang mengatur kepemilikan senjata api di Indonesia, khususnya Undang-Undang Darurat Nomor 12 Tahun 1951, memberikan sanksi pidana yang berat bagi pelanggaran, termasuk ancaman hukuman mati dan penjara seumur hidup. Kesadaran masyarakat mengenai peraturan kepemilikan senjata api masih rendah, yang berkontribusi terhadap tingginya angka kepemilikan senjata api ilegal. Serta penegakan hukum terhadap kepemilikan senjata api ilegal pada berbagai hambatan, termasuk izin pengawasan dari pihak kepolisian dan kepatuhan masyarakat yang minimal dalam menyerahkan senjata api ilegal.